MODERN TECHNOLOGIES FOR APPLYING ACRYLIC COMPOSITION TO THE SURFACE OF CONCRETE TO CONNECT BUILDING STRUCTURES - Zolotova, N.; Suprun, О. (Municipal economy of cities. Series: «Economy science», 2023)
The article reviews and analyzes modern equipment and technological solutions for applying an acrylic composition to a concrete surface, the composition of which was developed at the O.M. Beketov Kharkiv National University of Urban Economy. The composition is used to connect concrete building structures in the construction of building facilities. The adhesive and cohesive properties of acrylic compositions make it possible to reduce the time required to put facilities into operation, and to carry out repair and restoration work practically without stopping production. The joints of concrete building structures using acrylic compositions are characterized by more efficient parameters compared to known solutions using other adhesive compositions. The use of acrylic adhesive compositions helps to reduce the time of construction, reconstruction and repair of buildings and structures, save material, labor and financial resources, which is most important when repairing and reconstructing existing buildings and structures for various purposes. The article discusses the application of an acrylic composition to the surface of old concrete with large volumes of work - by a mechanized method. It is determined that for a more efficient connection of building structures, it is most expedient to use acrylic compositions developed and proposed for use in construction by scientists аt the O. M. Beketov National University of Urban Economy in Kharkiv The article focuses on the application of acrylic compositions to the surface of old concrete with large volumes of work - by a mechanized method. It is proved that it is advisable to use the AIRMIX technology, which is a combination of two methods of pneumatic and airless (AIRLESS) spraying of materials on any surface of a building structure. It has been determined that the use of Airmix equipment sets is characterized by quite high performance when applying an acrylic composition to the concrete surface, such as material efficiency, quality of the resulting layer, and high productivity of the work performed.